The Influence of Argument Quality and Information Richness on Trust in Halal Cosmetic Reviews - Rahma Haryono, Aufa Aviska; Susilowati, Fitriah Dwi; Mardiana, Lena; Rahmatika, Febrina; Rohmah, Resy Nur (Institut Agama Islam Negeri Ponorogo, 2023)
In the digital age, halal cosmetic products are becoming increasingly popular. Online reviews play an important role in consumers' purchasing decisions, as they cannot see and check the quality of the products directly, but only through the screens of their gadgets. Under Islamic law, the consumption of halal cosmetics is not only obligatory but also a lifestyle choice. The purpose of this study was to examine the effect of argument quality and information richness on perceptions of information quality and trustworthiness of halal product reviews on the Shopee platform. We utilized a survey design involving 120 participants and applied ANOVA with a regression approach for analysis. Our results show that argument quality and information richness have a positive impact on perceived information quality. Furthermore, perceived information quality positively affects trust in halal product reviews. The results highlight the importance of providing high quality arguments and information in online reviews to increase consumer trust in halal cosmetic products. Furthermore, this study highlights the role of the Shopee platform in shaping consumer perceptions of online reviews, especially in the context of halal cosmetics. Marketers can use these findings to enhance their brand credibility and increase consumer trust through high-quality online product reviews. This study is useful for muslim marketers so that they can increase sales by motivating consumers to provide quality reviews that can be adopted by other consumers.